Duration of labor stages and pregnancy outcomes in vaginal birth after cesarean: a retrospective comparative analysis - Zhu, Tianying; Luo, Dan; Li, Yan; Xiong, Liling (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to characterize the labor duration distribution and evaluate maternal-neonatal outcomes of vaginal birth after cesarean (VBAC) under epidural anesthesia.MethodIn this retrospective comparative study, we analyzed 156 term singleton VBAC cases with epidural anesthesia at Chengdu Women’s and Children’s Central Hospital (January 2021–December 2024), matched 1:1 by age to nulliparous controls. Comparative analyses of baseline characteristics, pregnancy complications, delivery modes, pregnancy outcomes, and labor durations were performed using independent t-tests, Mann–Whitney U tests, and χ2/Fisher’s exact tests. VBAC cases were stratified by prior labor attempt (n = 25 with vs. n = 131 without) to assess its impact on labor progression, with Spearman tests evaluating inter-stage correlations.ResultsDemonstrated that VBAC cases had significantly higher median 24 h postpartum blood loss (330 vs. 250 mL), postpartum hemorrhage rates (43% vs. 20%), and neonatal NICU admission rates (10% vs. 2%) compared to nulliparous controls (all p < 0.05). The 95th percentile durations for VBAC were 730 min (first stage) and 81 min (second stage), both significantly shorter than controls (p < 0.05), while third-stage durations were comparable (95th percentile, 11 vs. 10 min, p > 0.05). Prior labor attempt did not influence VBAC labor progression (p > 0.05). Positive correlations existed between first and second stages in both groups (r = 0.297, p = 0.002).ConclusionThese results suggest that VBAC under epidural anesthesia may progress faster through first and second stages of labor than nulliparous deliveries but carries higher risks of adverse outcomes. Clinical management should integrate multifactorial assessment, warranting further investigation into labor patterns and outcome relationships.